El impacto de la jurisprudencia del Tribunal de Justicia de la Unión Europea en la definición del principio de libre circulación de mercancías en la Comunidad Andina y el Mercosur - Reyes Tagle, Yovana (2018)
The Andean Court of Justice (ACJ) and the Permanent Tribunal of Review (PTR) of Mercosur have used the European Court of Justice (ECJ) case law to define the principle of free movement of goods enshrined in the Cartagena Agreement and the Treaty of Asuncion. This paper seeks to analyze the manner in which the ACJ and the PTR have applied the ECJ case law in order to determine the existence of trade restrictions. It is argued that there is a need to developed a contextual interpretation of the principle of free movement of goods in the Andean Community and Mercosur that clarifies and develop the concepts of the Cartagena Agreement and the Treaty of Asuncion in the light of their own integration processes, of which the ACJ and the PTR are part.